Advances in cholera research: from molecular biology to public health initiatives - Walton, Madison G.; Cubillejo, Isabella; Nag, Dhrubajyoti; Withey, Jeffrey H. (Frontiers in Microbiology, 2023)
The aquatic bacterium Vibrio cholerae is the etiological agent of the diarrheal disease cholera, which has plagued the world for centuries. This pathogen has been the subject of studies in a vast array of fields, from molecular biology to animal models for virulence activity to epidemiological disease transmission modeling. V. cholerae genetics and the activity of virulence genes determine the pathogenic potential of different strains, as well as provide a model for genomic evolution in the natural environment. While animal models for V. cholerae infection have been used for decades, recent advances in this area provide a well-rounded picture of nearly all aspects of V. cholerae interaction with both mammalian and non-mammalian hosts, encompassing colonization dynamics, pathogenesis, immunological responses, and transmission to naïve populations. Microbiome studies have become increasingly common as access and affordability of sequencing has improved, and these studies have revealed key factors in V. cholerae communication and competition with members of the gut microbiota. Despite a wealth of knowledge surrounding V. cholerae, the pathogen remains endemic in numerous countries and causes sporadic outbreaks elsewhere. Public health initiatives aim to prevent cholera outbreaks and provide prompt, effective relief in cases where prevention is not feasible. In this review, we describe recent advancements in cholera research in these areas to provide a more complete illustration of V. cholerae evolution as a microbe and significant global health threat, as well as how researchers are working to improve understanding and minimize impact of this pathogen on the vulnerable populations.